Popularización del futbol en Buenos Aires: “¿Cómo llamaremos a nuestro club?” - Frydenberg, Julio D. (El Colegio de México, A.C., 2022)
The objective of this article is to explore the process of adopting the practice of soccer. It is based on an analysis of the sports section of the newspaper La Argentina, as well as data from the so-called traditional history of Argentinean soccer, which reflect the first—sometimes informal—steps taken by certain clubs, centered on the names they were given by their young founders. The analysis of these expressions and decisions will allow for a clearer vision of the ideas and affects that mobilized these soccer players and could constitute a path to testing a world that is difficult to assimilate by simply looking backward. This analysis provides clues to the identitarian scenarios that drew them together and the mental and emotional states of the capital’s youth, a tone which seems to have survived in the soccer world until the present day in an ebb and flow, and even in backwaters that resist change.